Climate change, large risks, small risks, and the value per statistical life - Anna Alberini; Milan Ščasný (Charles University in Prague, Institute of Economic Studies (IES), 2024)
We conduct a contingent valuation survey in Spain and the UK to elicit information about the Willingness to Pay (WTP) for heat wave watch and response programs. We find that people are willing to pay for such programs, and that the WTP ( exteuro 50 for each of 10 years; 2019 PPP euro) is virtually the same across the two countries and across respondents that received two alternate presentations of the mortality risks with and without the programs. The responses to the WTP questions are internally consistent. Persons who re-assessed their own risks as "very high" after reading the questionnaire's information about the health effects of excessive heat are prepared to pay more for these programs. These persons are in poor health and less highly educated, and thus an important priority for outreach and education efforts by heat wave watch and response programs. That people value saving lives during heat waves as important is confirmed by the results of person tradeoffs, which show that avoiding a fatality during heat waves is comparable to avoiding a cancer fatality, is slightly more valuable than an avoiding a cardiovascular fatality, and definitely more valuable than an avoided road traffic fatality. The Value per Statistical Life implied by the WTP for the programs is exteuro 1.1 million to exteuro 4.7 million (2019 PPP euro), depending on the size of the mortality risk reduction valued by the respondent, for an average of exteuro 1.6 million.
Keywords: Q51; Q54; Q58; K32; 330; Climate Change; Heat Waves; Health Risks; Value per Statistical Life (VSL); Life-saving Programs